Harmonisasi Antara Lembaga Yudikatif Mahkamah Konstitusi dan Mahkamah Agung dalam Dinamika Hukum Tata Negara: Analisis Terkait Keseimbangan Kekuasaan Di Indonesia - Abdul Aziz Nurambiya, Muhammad; Tiopan, Demson (UNES Law Review, 2023)
The purpose of this research is to analyse how the balance of power in Indonesia is reflected through the harmonisation of judicial institutions, namely between the Constitutional Court (MK) and the Supreme Court (MA). This research is written through a normative juridical approach by relying on existing secondary data. The result of this research is that harmonisation between the Constitutional Court (MK) and the Supreme Court (MA) plays an important role in maintaining the balance of power in Indonesia, especially in the context of constitutional law. There is disharmony between the two institutions in several decisions, such as in the case of the nomination of DPD RI candidates in the 2019 simultaneous elections, which shows the need for better coordination between the two institutions to ensure clarity and harmony in constitutional law regulations. Proper coordination between the Constitutional Court and the Supreme Court, such as in the case of interfaith marriage, can provide clarity and harmony in regulations. In addition, efforts to maintain harmonisation between the Constitutional Court and the Supreme Court also include amending the 1945 Constitution and ensuring that decisions or actions of other government institutions remain within the corridors of the law. This shows the need for the aforementioned concrete efforts to strengthen cooperation between the two institutions in order to achieve harmonisation in Indonesia's legal system.